Mental health and help-seeking in Czech sexual minorities: a nationally representative cross-sectional study - Pitoňák, Michal; Potočár, Libor; Formánek, Tomáš (Epidemiology and psychiatric sciences, 2024)
AIMS: The mental health of sexual minority (SM) individuals remains overlooked and understudied in Czechia. We aimed to estimate (1) the prevalence rate and (2) the relative risk of common mental disorders and (3) the mental distress severity among the Czech SM people compared with the heterosexual population. In addition, we aimed to investigate help-seeking for mental disorders in SM people. METHODS: We used data from a cross-sectional, nationally representative survey of Czech community-dwelling adults, consisting of 3063 respondents (response rate = 58.62%). We used the Mini-International Neuropsychiatric Interview to assess the presence of mental disorders. In individuals scoring positively, we established help-seeking in the past 12 months. We assessed symptom severity using the 9-item Patient Health Questionnaire and the 7-item Generalized Anxiety Disorder scale. We computed the prevalence of mental disorders and the treatment gap with 95% confidence intervals. To assess the risk of having a mental disorder, we used binary logistic regression. RESULTS: We demonstrated that the prevalence of current mental disorders was 18.85% (17.43-20.28), 52.27% (36.91-67.63), 33.33% (19.5-47.17) and 25.93% (13.85-38) in heterosexual, gay or lesbian, bisexual and more sexually diverse individuals, respectively. Suicidal thoughts and behaviours were present in 5.73% (4.88-6.57), 25.00% (11.68-38.32), 22.92% (10.58-35.25) and 11.11% (2.45-19.77) of heterosexual, gay or lesbian, bisexual and more sexually diverse individuals, respectively. After confounder adjustment, gay or lesbian individuals were more likely to have at least one current mental disorder compared with heterosexual counterparts (odds ratio = 3.51; 1.83-6.76). For bisexual and sexually more diverse individuals, the results were consistent with a null effect (1.85; 0.96-3.45 and 0.89; 0.42-1.73). The mean depression symptom severity was 2.96 (2.81-3.11) in heterosexual people and 4.68 (2.95-6.42), 7.12 (5.07-9.18) and 5.17 (3.38-6.95) in gay or lesbian, bisexual and more sexually diverse individuals, respectively. The mean anxiety symptom severity was 1.97 (1.85-2.08) in heterosexual people and 3.5 (1.98-5.02), 4.63 (3.05-6.2) and 3.7 (2.29-5.11) in gay or lesbian, bisexual and more sexually diverse individuals, respectively. We demonstrated broadly consistent levels of treatment gap in heterosexual and SM individuals scoring positively for at least one current mental disorder (82.91%; 79.5-85.96 vs. 81.13%; 68.03-90.56). CONCLUSIONS: We provide evidence that SM people in Czechia have substantially worse mental health outcomes than their heterosexual counterparts. Systemic changes are imperative to provide not only better and more sensitive care to SM individuals but also to address structural stigma contributing to these health disparities.
Keywords: dospělí; Česká republika; duševní zdraví; sexuální a genderové menšiny; homosexualita ženská; lidé; Female; Sexual and Gender Minorities; Cross-Sectional Studies; Mental Health; Czech Republic; Adult; Homosexuality, Female; ženské pohlaví; průřezové studie; Humans